2016
DOI: 10.4103/0366-6999.193452
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-210 Plays a Critical Role in the Angiogenic Effect of Isoprenaline on Human Umbilical Vein Endothelial Cells via Regulation of Noncoding RNAs

Abstract: Background:β-adrenoceptors play a crucial regulatory role in blood vessel endothelial cells. Isoprenaline (ISO, a β-adrenergic agonist) has been reported to promote angiogenesis through upregulation of vascular endothelial growth factor (VEGF) expression; however, the underlying mechanism remains to be investigated. It is widely accepted that certain noncoding RNAs, including microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), can regulate endothelial cell behavior, including their involvement in angiogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…A previous study demonstrated that overexpression of miR‐210 reduced maternally expressed 3 (MEG3) expression (Y.‐Y. Yan et al, ). MEG3 was reported to be downregulated in 80% of preeclampstic placentas (Song et al ().…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that overexpression of miR‐210 reduced maternally expressed 3 (MEG3) expression (Y.‐Y. Yan et al, ). MEG3 was reported to be downregulated in 80% of preeclampstic placentas (Song et al ().…”
Section: Discussionmentioning
confidence: 99%
“…Further research indicated that miR‐210 facilitates angiogenesis through negatively regulating the target gene, ephrin A3, which is an important member of the ephrin angiogenesis regulatory gene family 51, 91, 92. Moreover, a study revealed that isoprenaline enhances the levels of miR‐210, miR‐21 and miR‐1 and decreases those of the lncRNAs maternally expressed 3 (MEG3) and growth arrest‑specific transcript 5 (GAS5), thereby improving angiogenesis 93. The inhibition of miR‐210 increases tumour cell apoptosis and autophagy and represses angiogenesis 94.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…Furthermore, knockdown of MALAT1 in vivo inhibited proliferation of endothelial cells and reduced neonatal retina vascularization (Michalik et al, 2014). In addition, Yan Y.Y. et al (2016) have found arrest-specific transcript 5 (GAS5) and Meg3 were significantly downregulated in isoprenaline treated HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…It is part of the DLK1-Meg3 locus located on human chromosome 14q32 (Miyoshi et al, 2000) and was believed to be associated with ECs’ injury (Zhang et al, 2003). Its expression level was also found to be related to downregulation in isoprenaline treated HUVECs (Yan Y.Y. et al, 2016).…”
Section: Introductionmentioning
confidence: 98%